2014
DOI: 10.1590/s0100-06832014000400010
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxides and quality of organic matter in sugarcane harvesting systems

Abstract: Improvements in working conditions, sustainable production, and competitiveness have led to substantial changes in sugarcane harvesting systems. Such changes have altered a number of soil properties, including iron oxides and organic matter, as well as some chemical properties, such as the maximum P adsorption capacity of the soil. The aim of this study was to characterize the relationship between iron oxides and the quality of organic matter in sugarcane harvesting systems. For that purpose, two 1 ha plots in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…(9-21 nm) peaks lower than Hm111 (12-25 nm) and Hm012 (30-89 nm) peaks revealed the persistence of the crystalline Hm in relation to Gt, a common characteristic in tropical soils (Inda Júnior and Kämpf, 2005;Barbieri et al, 2014) clearly observed in the transport foothill, where peaks referring to the face of Hm012 are well-defined and narrow (Figure 4). The climatic conditions of the Amazon, especially precipitation and temperature, combined with the natural increase of OM, acid pH (Table 2), and intense microbial activity, contribute to a higher presence of Al in the goethite structure, which decreases its crystallinity.…”
Section: Mineralogical Attributesmentioning
confidence: 92%
“…(9-21 nm) peaks lower than Hm111 (12-25 nm) and Hm012 (30-89 nm) peaks revealed the persistence of the crystalline Hm in relation to Gt, a common characteristic in tropical soils (Inda Júnior and Kämpf, 2005;Barbieri et al, 2014) clearly observed in the transport foothill, where peaks referring to the face of Hm012 are well-defined and narrow (Figure 4). The climatic conditions of the Amazon, especially precipitation and temperature, combined with the natural increase of OM, acid pH (Table 2), and intense microbial activity, contribute to a higher presence of Al in the goethite structure, which decreases its crystallinity.…”
Section: Mineralogical Attributesmentioning
confidence: 92%
“…The absorption of P by plants is directly related to its availability, which in turn is influenced by texture, fertilizer dose and by the time of contact with the soil (Vieira et al, 2015). For their part, Oliveira et al (2014) and Barbieri et al (2013) highlights n that the higher the clay content in the soil, the higher the adsorption of the P and lower availability. Contact d the P in the solution of the soil with the root is performed almost exclusively by diffusion process in which the element translocate short distances in a stationary aqueous phase, called solution soil, for the concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have shown that goethite (Gt = α-FeOOH) and gibbsite (Gb = γ-Al(OH) 3 ) rich soils provide higher P-fixing power than hematite-governed soils (Hm = α-Fe 2 O 3 ) and, secondarily, kaolinite (Kt) (Broggi, Oliveira, F. J. Freire, M. B. G. S. Freire, & Nascimento, 2011;Barbieri et al, 2014). In a pioneer study developed in the Brazilian Cerrado, Novais and Smyth (1999) found in clayey Latosols more than 2 mg cm -3 of adsorbed P, which is equivalent to 4000 kg ha -1 of P, that is, 9.200 kg ha -1 of P 2 O 5 , incorporated at 0-20 cm.…”
Section: Introductionmentioning
confidence: 99%